PENGARUH FAKTOR EKSTERNAL DAN INTERNAL TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH - Silvi Novita Dewi; Erma Setiawati (LPPM Universitas Bina Bangsa, 2024)
This research aims to test whether there is an independent influence of gross domestic product, inflation, interest rates, financing to deposit ratio and operating efficiency ratio on return on assets. The population in this research is Islamic commercial banks in Indonesia. The number of samples in this study was 36 respondents. The sampling technique uses a purposive sampling method. The research method used is quantitative with the data source in the form of primary data. The data analysis method uses multiple linear regression analysis with SPSS version 25. The results of this research provide empirical evidence that partially the independent variables gross domestic product (GDP), inflation, interest rates, and financing to deposit ratio (FDR) have no effect on return on assets (ROA). Simultaneously, the independence variable operating efficiency ratio (OER) has a significant effect on return on assets (ROA)